Temporal analysis of remotely sensed image sequences - DaPonte, John S.; Vitale, Joseph N.; Parikh, Jo Ann; Tselioudis, George (Remote Sensing, 1999)
Temporal analysis has been applied to a sequence of cloud top pressure (CTP) images and cloud optical thickness (TAU) images stored in the International Satellite Cloud Climatology Project (ISCCP) D1 database located at the NASA Goddard Institute for Space Studies (GISS). Each pixel in the D1 data set has a resolution of 2.5 degrees or 280 kilometers. These images were collected in consecutive three-hour intervals for the entire month of April 1989. The primary objective of this project was to develop a sequence of storm tracks from the satellite images to follow the formation, progression and dissipation of storm systems over time. Composite images where created by projecting ahead in time and substituting the first available valid pixel for missing data and a variety of CTP and TAU cut-off values were used to identify regions of interest. Region correspondences were determined from one time frame to another yielding the coordinates of storm centers. These tracks were compared to storm tracks computed from sea level pressure data obtain from the National Meteorological Center (NMC) for the same time period. The location of sea level storm center provides insight as to whether storms have occurred anywhere in a region and can be helpful in determining the presence or absence of storms in a general geographic region.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00225 tex.type: [object Object]
Keywords: Climatology; Cloud optical thickness; Cloud top pressure (CTP) images; Clouds; Communication satellites; Remote sensing; Storms; dept.csc